Chip-based nano-LC-MS/MS identification of proteins in complex biological samples using a novel polymer microfluidic device - Srbek, Jan; Eickhoff, Jan; Effelsberg, Uwe; Kraiczek, Karsten; van de Goor, Tom; Coufal, Pavel (Journal of separation science, 2007)
Although the proteome of each organism is unambiguously coded in its genome, the proteome shows the real biology in action in each particular organism. New powerful tools are being developed for biochemists and biologists to analyze complex biological samples for studying the complete protein supplement of the genome, i. e., the proteome. There are several methods available for proteome analysis including 2-DE and several forms of MS. In recent years, technologies such as microfluidics and array-based systems have appeared in the field of analysis, identification, and quantification of proteins. These novel approaches might help in solving current technical challenges in proteomics. This paper presents a practical application of the first commercially available microfluidic nano-ESI device coupled with nano-LC (i. e., HPLC-chip) for the analysis of samples of some biological protein mixtures.
Keywords: Chromatography, Liquid; Humans; Mass Spectrometry; proteiny; rýže (rod); Molecular Sequence Data; testování materiálů; molekulární sekvence - údaje; mikrofluidní analytické techniky; Proteins; Microfluidic Analytical Techniques; lidé; Seeds; Oryza; chromatografie kapalinová; Lens Plant; hmotnostní spektrometrie; semena rostlinná; čočka; Materials Testing